Ex vivo evaluation of the effectiveness of XP-endo Finisher on the removal of smear layer from the root canal - Sângela Maria PEREIRA; Ceci Nunes CARVALHO; Rudys Rodolfo TAVAREZ; Paulo NELSON-FILHO; Léa Assed Bezerra DA SILVA; Etevaldo Matos MAIA FILHO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Objective: The aim of this study was to evaluate the effectiveness of XP-endo Finisher (XP) on removal of the smear layer in root canals by comparing different irrigation protocols. Methods: Seventy-two human single-rooted teeth were similarly instrumented using R25 Reciproc files (VDW, Munich, Germany) applied in reciprocating mode with a VDW GOLD endo motor (VDW, Munich, Germany). The working length was determined at 1 mm short of the apical foramen. The canals were irrigated with 5 mL of 2.5% sodium hypochlorite during instrumentation. The teeth were divided at random into six groups (n=12). A control group, which was not submitted to the final irrigation protocol, and five experimental groups with different irrigants and agitation techniques: EDTA/File, EDTA/XP, EDTA/Passive Ultrasonic Irrigation (PUI), Distilled Water (DW)/XP, and DW/PUI). Smear layer removal quality scores were assessed in the apical, middle, and cervical thirds of the root canal based on images obtained by scanning electron microscopy. Data were analyzed using the Kruskal-Wallis test, followed by two-by-two comparisons with the Dunn test (α=5%). Results: EDTA/File, EDTA/PUI, and EDTA/XP groups demonstrated significantly lower scores than the other groups (P<0.05) in all thirds evaluated. No significant difference was observed between the groups in which distilled water was used and the control group in all thirds evaluated (P> 0.05). Conclusion: The XP-endo Finisher file did not increase the efficiency of EDTA in removal of the smear layer in root canals.